Study to assess the economic impact of tourism on selected CDB borrowing member countries : final report ([s.n.] [S.l.], 1996)
Reviews the literature on tourism impacts in the Caribbean and describes global tourism competitive conditions. Presents the Limited Input-Output model that is intended to measure impact and discusses the macroeconomic indicators and development common to the three countries. Describes conditions and impacts in Barbados, Dominica and St. Vincent and the Grenadines, also discusses data sources and issues in the three countries.
DC